IMPLEMENTASI PRINSIP RESTORATIVE JUSTICE BERDASARKAN VICTIM ORIENTED DALAM DIVERSI GUNA PENYELESAIAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK (Studi Pada Unit PPA Satreskrim Polres Pesisir Selatan) - Umar Dinata (LPPM Universitas Ekasakti Padang, 2020)
Victim-oriented restorative approaches to diversion have not yet been fully implemented. In practice the results of diversion pay more attention to the interests of the perpetrators than the interests of the victims. The diversion agreement obtained is in the form of a return on losses in the event of a victim; medical and psychosocial rehabilitation; Submission to parents / guardians; participation in education or training in educational institutions or LPKS (Institutions of all forms of agreement above are still oriented to the perpetrators. Recovery of victims is only a stipulated requirement as far as possible to distance the perpetrators from punishment. obstacles in applying the victim-oriented concept of restorative justice, namely: Family attitudes the victim in his participation resolved the case through the concept of Restorative Justice and there was pressure from the investigator against the victim to accept the results of the diversion.